1996
DOI: 10.1007/s002130050138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term haloperidol administration enhances and short-term administration attenuates the behavioral effects of cocaine in a place conditioning procedure

Abstract: Many behavioral effects of cocaine are attenuated by dopamine (DA) receptor antagonists. Yet, long-term DA antagonist administration enhances neuronal responsiveness to DA in several pathways, including the mesolimbic system. This study compared the effects of short-term versus long-term administration of the DA antagonist, haloperidol, on cocaine place conditioning. In the short-term study, rats were maintained on haloperidol or vehicle for the 10 days of place conditioning. Place conditioning to moderate dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Although acute administration of dopamine D1 or D2 antagonists can block cocaine's reinforcing and discriminative-stimulus effects, repeated antagonist administration can increase cocaine's reinforcing (self-administration) and rewarding (conditioned place preference) effects in rats (Emmett-Oglesby and Mathis 1988; Kosten et al 1996;Kosten 1997).…”
Section: Rodents and Non-human Primatesmentioning
confidence: 99%
“…Although acute administration of dopamine D1 or D2 antagonists can block cocaine's reinforcing and discriminative-stimulus effects, repeated antagonist administration can increase cocaine's reinforcing (self-administration) and rewarding (conditioned place preference) effects in rats (Emmett-Oglesby and Mathis 1988; Kosten et al 1996;Kosten 1997).…”
Section: Rodents and Non-human Primatesmentioning
confidence: 99%
“…Animal studies have suggested that repeated exposure to many psychiatric medications alters the density of neurotransmitter receptors, including several receptors implicated in the response to cocaine. Longterm exposure to haloperidol alters the behavioral response of rats to cocaine [99,100]. Furthermore, a recent study reported that long-term ziprasidone increased cocaine toxicity [101].…”
Section: Cocaine Toxicity: Tying Together Concentrations and Receptormentioning
confidence: 99%
“…Haloperidol and clozapine were administered at target doses of 1.8 and 35-40 mg/kg/day, respectively, as used previously (Fitzgerald et al, 1995). This treatment method has been shown to produce consistent and clinically relevant plasma levels of these drugs (Kosten and Nestler, 1994;Fitzgerald et al, 1995;Kosten et al, 1996). In one experiment, haloperidol treatment was continued, at a target dose of 1.5 mg/kg/day, for a total of 24 weeks.…”
Section: Drug Administrationmentioning
confidence: 99%